Monitoring of Domestic Wastewater Treatment PT. Perkebunan Karet (Rubber Plantation Ltd.) - Fajriharish Nur Awan; Khairattul Nabila; Dewi Erowati (Indonesian Journal of Environmental Management and Sustainability, 2022)
West Sumatera is one of the provinces in Indonesia that has an excellence in agricultural commodities. One of the agricultural products in West Sumatera is natural rubber. In addition to producing rubber, in West Sumatera there are also several rubber plantation processing industries, one of which is PT. Perkebunan Karet (Rubber Plantation Ltd.). In every activity PT. Perkebunan Karet (Rubber Plantation Ltd.) produces liquid waste that comes from domestic activities. The purpose of the research is to identify sources of domestic wastewater, identify liquid waste treatment processes at domestic wastewater treatment plants, identify liquid waste quality before and after treatment and calculate the eciency of domestic wastewater treatment. The method used is the method of observation and interviews and analysis of data processing using descriptive analysis. The results of this study are the source of domestic wastewater PT. Perkebunan Karet (Rubber Plantation Ltd.) comes from public toilet facilities, company oces, employee mess, control and document center oces, laboratories, dining rooms and canteens. The stages of domestic wastewater treatment include oil and grease traps, sedimentation, ltration, and disinfection. The eciency of reducing the quality of domestic wastewater on average from January to June for parameters BOD 50.54%, COD 15.79%.